Internalisasi Nilai-Nilai Religius bagi Peserta Didik - Zailiah, Siti (STAI Denpasar Bali, 2023)
This article discusses the internalization of religious values for students, research studies through literature review, with research design as a guideline in conducting research to achieve research objectives. Literature review research begins with identifying problems, then collecting libraries and screening the libraries obtained, then the data obtained will be presented in the form of data tabulations and analyzed. Based on the analysis that has been carried out that the internalization of religious values for students can be instilled through several activities such as imtaq activities which include the value of worship with mahdoh worship, through congregational prayers, zakat fitrah expenditure, while ghoiru mahdoh is through the slaughter of sacrificial animals, arofah camps or free medicine and social services in orphanages and istighosah. The value of jihad (ruhul jihad) is earnestly seeking knowledge in the classroom and outside the classroom. The value of trust by obeying all rules and being responsible and sincere with jariyah charity, social services. The moral value of politeness, meeting teachers greeting and shaking hands and discipline by worshiping on time, leaving school on time, and the value of example by setting a good example to students, so teachers are also khotmil and get spiritual flush from the principal. The strategy of internalizing religious values for students through imtaq activities is divided into two, namely inside the classroom and outside the classroom.